Argentina (Revenue Statistics in Latin America and the Caribbean)
This dataset contains tax revenue collected by Argentina. It provides detailed tax revenues by sector (Supranational, Federal or Central Government, State or Lander Government, Local Government, and Social Security Funds) and by specific tax, such as capital gains, profits and income, property, sales, etc